Perubahan Organisasi Perguruan Tinggi Era IT - Hetwi Marselina Saerang; H.N.Tambingon; Shelty Deity Meity Sumual (Syntax Corporation Indonesia, 2024)
Changes in the use of technology are underway in the world of education. There are three main changes underway at the moment, namely (1), the emergence of extensive use of technology, (2), the transition of technology use in the High Desert, (3), the introduction of a national curriculum with the use of Information Communication and Technologies (ICT) systems. Organizational change can be thought of as having cycles with four phases: (1), the generation of ideas and inventions; (2), selection of ideas; (3), implementation of ideas; and (4), the diffusion of ideas. Organizational change offers benefits and can include the introduction of knowledge. Therefore, how do people see the word 'change' in higher education, Change means many new, and creative things for the development of education, so that the old way is no longer effective. The 2022 national curriculum has used the